1993
DOI: 10.1029/93wr00341
|View full text |Cite
|
Sign up to set email alerts
|

Lmoment diagrams should replace product moment diagrams

Abstract: It is well known that product moment ratio estimators of the coefficient of variation Cν, skewness γ, and kurtosis κ exhibit substantial bias and variance for the small (n ≤ 100) samples normally encountered in hydrologic applications. Consequently, L moment ratio estimators, termed L coefficient of variation τ2, L skewness τ3, and L kurtosis τ4 are now advocated because they are nearly unbiased for all underlying distributions. The advantages of L moment ratio estimators over product moment ratio estimators a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
229
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 386 publications
(238 citation statements)
references
References 14 publications
1
229
0
8
Order By: Relevance
“…They are commonly estimated by the method of moments (Chow, 1964;Rao and Hamed, 2000), although they can also be estimated by L-moments (Greenwood et al, 1979). The method of L-moments was preferred here because it yields more robust estimations than conventional moments (Vogel and Fennessey, 1993;Sankarasubramanian and Srinivasan, 1999). Hosking (1990) explains in detail the estimation of parameters using L-moments.…”
Section: Extreme Dry-spell Modelling With Annual Maximum Series and Gmentioning
confidence: 99%
“…They are commonly estimated by the method of moments (Chow, 1964;Rao and Hamed, 2000), although they can also be estimated by L-moments (Greenwood et al, 1979). The method of L-moments was preferred here because it yields more robust estimations than conventional moments (Vogel and Fennessey, 1993;Sankarasubramanian and Srinivasan, 1999). Hosking (1990) explains in detail the estimation of parameters using L-moments.…”
Section: Extreme Dry-spell Modelling With Annual Maximum Series and Gmentioning
confidence: 99%
“…On the same plot, the theoretical relationships for various probability density functions are compared to the observations. Vogel and Fennessey (1993) have shown that L-moment ratio diagrams are nearly always an improvement over ordinary moment ratio diagrams because L-moment ratios are approximately unbiased, whereas ordinary moment ratios can exhibit enormous downward bias, particularly for skewed samples, even with extremely large samples. Hosking (1990), Stedinger et al (1993), Hosking and Wallis (1997), and others have summarized the theory of L-moments, thus we do not reproduce the theory here.…”
Section: The Theory Of L-momentsmentioning
confidence: 99%
“…LH-moments are the extension or generalization of L-moments, which are defi ned as the linear combination of higher order statistics introduced by Wang [12]. Product moments and moment ratios have been found to be sensitive to the upper part of distributions and thus sample outliers [39]. The L moments are oversensitive to the lower part of distributions and give insuffi cient weight to large sample values that actually contain useful information on the upper distribution tail [12].…”
Section: Methodsmentioning
confidence: 99%